Tinitus Pada Lansia - Indra Zachreini; Angie Delashynta Rianda (Jurnal Anestesi, 2023)
Tinnitus is a symptom of an associated disease process, which may have a major impact on daily life. With an aging population worldwide, it is important to gain insight into the occurrence of tinnitus at an older age. Several studies have observed that variables such as alcohol or smoking are not significantly associated with tinnitus. Whereas in otic, sinonasal pathology, dizziness, hypertension or arteriosclerosis as a significant correlation. Imaging and activity measurement technology related to tinnitus in the ear, auditory nerve, and auditory canal of the brain. Although many therapeutic modalities have been applied, there is no consensus regarding effective therapeutic agents. Although medication does not necessarily relieve tinnitus, accurate diagnosis and treatment are important to reduce the disturbance associated with tinnitus and to prevent additional disability.